TEBARKAN SENYUM, TOLAK BULLYING, INDONESIA DAMAI - Nafisatul Hasanah; Violen Anjeli Anggraini; Agnes Jocelyn; Aloysius Edward; Hendra Wijaya; Renita Millena; Kaoling Kaoling; Angelline Tu; Herlina Herlina (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Internasional Batam, 2020)
Bullying is an act of hurt that often occurs among teenagers. Adolescents in the age range of 12-17 years are the times when they find their identity, they are still easily affected by their emotions and their surroundings. The act of bullying will have a very bad impact on victims, starting from the emergence of a sense of distrust, depression, stress, and even causing death. That's why we need cooperation between parents, school, and friends to overcome this problem of bullying. Some of the efforts that have been made include being very ignorant, counseling, being advised by parents, but this does not necessarily change the child's heart. In this modern era, we take advantage of technological advances in order to alert teenagers to avoid bullying by creating videos by the author and some questions and prizes for teenagers who are able to complete well in the form of a smile-patterned mask.